Peran Ibu dalam Memotivasi Belajar Online Anak pada Masa Pandemi Covid-19 - Faikoh, Maharatun; Khasanah, Nur (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The role of mothers in motivating children's learning, which currently takes place online, the role of mothers is needed to motivate children. The purpose of this study is to be able to describe and realize the role of mothers in motivating children's online learning during the COVID-19 pandemic. This type of research is qualitative, descriptive research and uses analysis more often. Data analysis in this study is descriptive qualitative analysis. The process of collecting data in this study is using the methods of interview, observation, and documentation. The results of this study are themother's role in motivating children's online learning during the pandemic, including 1) the role of the mother as a child educator, 2) the mother's role as a child facilitator, 3) the mother's role as a child motivator, in providing motivation the roles that mothers do are, 1) giving gifts, 2) sayings of praise, 3) giving punishments. Furthermore, there are factors driving the mother's role in motivating children's online learning during the pandemic, namely 1) cooperation between family members, 2) the assertiveness of the mother, 3) the involvement of the father. The inhibiting factors for the mother's role in motivating children's online learning during the pandemic are 1) the condition of the child, 2) the mother's busyness, 3) the surrounding circumstances.